2014
DOI: 10.1128/jvi.01584-14
|View full text |Cite|
|
Sign up to set email alerts
|

Fine Mapping of Murine Antibody Responses to Immunization with a Novel Soluble Form of Hepatitis C Virus Envelope Glycoprotein Complex

Abstract: The hepatitis C virus (HCV) envelope glycoprotein E1E2 complex is a candidate vaccine antigen. Previous immunization studies of E1E2 have yielded various results on its ability to induce virus-neutralizing antibodies in animal models and humans. The murine model has become a vital tool for HCV research owing to the development of humanized mice susceptible to HCV infection. In this study, we investigated the antibody responses of mice immunized with E1E2 and a novel soluble form of E1E2 (sE1E2) by a DNA prime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 72 publications
8
60
0
Order By: Relevance
“…From the present study, the CD81bs front layer resembles a highly flexible loop despite being held by two disulfide bonds and despite high sequence conservation, which is generally not associated with flexible loops in viral proteins. High flexibility is consistent with the observation that soluble E2 and E1E2 can elicit antibodies that can bind the CD81bs with high affinity but, nonetheless, cannot neutralize the virus (27)(28)(29)(30)(31). Some of these non-NAbs or weak NAbs could be similar to mAb 8, which recognizes a conformation likely to be poorly accessible on the virus (Fig.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…From the present study, the CD81bs front layer resembles a highly flexible loop despite being held by two disulfide bonds and despite high sequence conservation, which is generally not associated with flexible loops in viral proteins. High flexibility is consistent with the observation that soluble E2 and E1E2 can elicit antibodies that can bind the CD81bs with high affinity but, nonetheless, cannot neutralize the virus (27)(28)(29)(30)(31). Some of these non-NAbs or weak NAbs could be similar to mAb 8, which recognizes a conformation likely to be poorly accessible on the virus (Fig.…”
Section: Resultssupporting
confidence: 56%
“…Third, antibody responses to the CD81bs are frequently detected in sera from subjects immunized with the candidate vaccine immunogens: soluble E2 or E1E2. However, these serum antibodies are often weak or nonneutralizing despite high anti-E1E2 antibody titers (14,(27)(28)(29)(30). Indeed, mAbs have been isolated to the different components of the CD81bs, but only a few (mentioned above) cross-neutralize the highly diverse HCV genotypes (30)(31)(32)(33).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…The resulting purified adenoviral bands were isolated using an 18.5-gauge needle and twice dialyzed against 4% sucrose. Adenovirus concentrations were measured at 10 12 times the dilution factor times the OD at 260 nm (27,28,(38)(39)(40). It was reported that N-glycans associated with HCV E2 could modulate receptor-binding affinity, as well as neutralizing-epitope recognition (41).…”
Section: Establishment Of Hcvcc Panels Covering Genotypes 1 Tomentioning
confidence: 99%